2012
DOI: 10.1111/maps.12012
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous and nonimpact origin of the Arkenu circular structures (al‐Kufrah basin—SE Libya)

Abstract: Abstract-The twin Arkenu circular structures (ACS), located in the al-Kufrah basin in southeastern Libya, were previously considered as double impact craters (the ''Arkenu craters''). The ACS consist of a NE (Arkenu 1) and a SW structure (Arkenu 2), with approximate diameters of about 10 km. They are characterized by two shallow depressions surrounded by concentric circular ridges and silica-impregnated sedimentary dikes cut by local faults. Our field, petrographic, and textural observations exclude that the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Most recently, Cigolini et al (2012) reported further evidence in support of a volcanic genesis of the Arkenu bodies from field and petrographic work. They did not observe shock metamorphic evidence in samples of sandstone from the Arkenu circular structures and also state clearly that the alleged shatter cones have an origin as wind-ablation features.…”
Section: The Impact Record Of Africamentioning
confidence: 91%
“…Most recently, Cigolini et al (2012) reported further evidence in support of a volcanic genesis of the Arkenu bodies from field and petrographic work. They did not observe shock metamorphic evidence in samples of sandstone from the Arkenu circular structures and also state clearly that the alleged shatter cones have an origin as wind-ablation features.…”
Section: The Impact Record Of Africamentioning
confidence: 91%
“…MISP opened to the public on March 19, 2005. Since its early years of activities, the museum staff operated not only in preserving and enhancing the meteorite collection through the development of cultural and educational activities but also in its enrichment through the organization of research expeditions in hot deserts—that is, Adrar and Erg Chech (Algeria), Hammadah al Hamra (Libya), Hadramawt (Yemen), Libyan desert in Egypt, al‐Kufra (Libya), Acfer (Algeria), Atacama (Chile)—to recover new specimens (Cigolini et al., 2012; Orti et al., 2010; Pratesi et al., 2005). Regarding the path choice in the exhibition area, MISP organized the meteorite collection on display, combining educational functions and aesthetic concerns with a perspective centered on the needs and interests of the visiting public (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…To mention only a few examples in the Arab world, the proposed impact structures of the two circular Arkenu structures in Libya (Paillou et al 2003), as well as a large field of multiple proposed impact craters in the Gilf Kebir region of southwestern Egypt (Paillou et al 2004), were proven as of non-impact but magmatic-endogenic origin during field work (Orti et al 2008;Cigolini et al 2012). The Lake Isli structure in the High Atlas Mountains of Morocco, recently interpreted by Ibhi et al (2013) as an impact crater because of the occurrence of lithic breccias, was shown to be related to tectonism and karst dissolution (Ibouh et al 2014).…”
mentioning
confidence: 99%